Integration between the Western and Islamic Parenting Models: Content Analysis in A Literature Review - Madyawati, Lilis; Nurjannah, Nurjannah; Che Mustafa, Mazlina (Jurnal Tarbiyatuna, 2023)
Parenting as a child care practice has become the main focus in both Western psychology and Islam psychology. Each perspective is founded on different values and contributes to the development of the parenting concept. The concept of parenting from the Western psychology includes Montessori parenting, positive parenting, and religious parenting. Meanwhile, from the perspective of Islam psychology, the concept of parenting involves prophetic parenting, Islamic parenting, Qur’anic parenting, and fathanah parenting. The researcher conducted a literature review on these concepts by collecting papers using search engines, including Google, Publish or Perish, and Open Knowledge Map and collected scientific journal articles that are nationally and internationally accredited. A total of 58 journal articles published between 2013 and 2023 were found. Data sampling is adjusted to the research topic, namely the concept of parenting and early childhood parenting. Next, the researcher will interpret the meaning of each journal article using content analysis to identify the basic argument of the research. The findings show that the development of the parenting concept in the Western psychology perspective stems from phenomena in parenting, especially the religion phenomenon in parenting culture in the 21st century. On the other hand, the development of the parenting concept in the Islam psychology perspective is merely a conceptual reinterpretation that is centered in the values of al-Qur’an and hadith. Nevertheless, the researcher found two patterns in the development of the parenting concept in Islam: first, the development of the parenting conceptual framework that is integrated with interpretation method on al-Qur’an texts to explain the notion of parenting, and second, the theoretical integration between the parenting concept that is in accordance with al-Qur’an and hadith and the Western psychology’s notion on parenting. Based on the literature review, the integration between the parenting concept in Western psychology perspective and that in Islam results in the SMART parenting model which prioritizes joy, education, moral and religion, and health for the children’s growth.